A neonate with meningitis caused by probiotic-related Clostridium butyricum - Yanfang Jiang; Jiaxu Yang; Yong Liu; Ying Liu; Wenli Zhou; Bin Yang; Bingxue Hu; Hui Wu (International Journal of Infectious Diseases)
Objectives: Clostridium butyricum (C. butyricum), a normal gut bacterium in humans, is commonly used as a probiotic. We described a 26-day-old premature neonate who was diagnosed with probiotic-related C. butyricum meningitis. Design: Upon the admission, suppurative meningitis was considered based on cerebrospinal fluid (CSF) biochemical test and neuroimaging examination, and C. butyricum was subsequently identified by CSF metagenomic next-generation sequencing. Given the history of administrating living C. butyricum products before admission, probiotics-associated suppurative meningitis was considered a high possibility, leading to the confirmation of anti-infection treatment including vancomycin and meropenem. Results: Following this therapy, the infant's CSF profiles demonstrated improvement. Additionally, further phylogenetic analysis confirmed the high homologous of C. butyricum from CSF with probiotics. Conclusions: This is the first report of C. butyricum infection in neonates, highlighting the importance for prudence in administrating probiotics for neonates, particularly in high-risk groups such as preterm infants, those with central venous catheters and intestinal diseases.